Perceptions of Junior High School Teachers and Students on English Language Instruction through the Merdeka Curriculum - Lailiy Kurnia Ilahi; Laily Fajariyah; Cristian Anggraini; Wahyudi Wahyudi; Endang Agus Sulasmi; Tutik Kurniawati (PT. Intelek Cendikiawan Nusantara, 2025)
The Independent Curriculum promotes varied intracurricular learning, allowing content to be delivered more effectively. This enables students to have ample opportunities to delve deeper into concepts and enhance their core competencies. At the same time, educators are given the autonomy to utilize a range of instructional strategies tailored to students’ interests and learning needs. This research investigates how teachers and students perceive the application of the Independent Curriculum in English language instruction at the junior high school level. It further explores the challenges encountered and the strategies employed to address these issues. Using a qualitative descriptive approach, data were gathered through interviews and classroom observations. Participants in this study included English language teachers, students from Grades 7 and 8, as well as the principal and vice principal of SMPN 1 Sumenep. Data analysis was conducted in three phases: reduction, display, and conclusion drawing. The findings indicate: (1) most teachers and students maintain a favourable view of the curriculum’s implementation and demonstrate comprehension aligned with its principles; (2) English language teaching is guided by structured learning modules and emphasizes the development of the Pancasila Student Profile as a key element of the curriculum. Educators primarily implement problem-based and project-based learning methods; and (3) challenges faced by educators include insufficient human resource readiness, complexities of differentiated instruction, limited digital literacy, inadequate learning materials, and student disengagement during lessons.